2020
DOI: 10.1002/aic.17078
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stoichiometry on the properties of exsolved Ni‐Fe alloy nanoparticles for dry methane reforming

Abstract: The dry reforming of methane has received notable attention as a chemical process to convert natural gas into value-added chemicals and fuels. Ni-based exsolution catalysts using perovskite oxides supports have been used for their attractive sinterresistance and coke-resistance properties. The perovskite oxide in itself has unique defect chemistry that can be used to manipulate and control the properties of the catalyst nanoparticles exsolved on the surface, therefore influencing both the nanoparticle and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 58 publications
0
30
1
Order By: Relevance
“…We examined the notion of bulk defect manipulation of perovskite oxide precursors to change the alloy composition, size, and shape of exsolved NiFe nanoparticles for DRM. 31 We found that the B-site metal redox properties can change nanoparticle formation and bulk crystal structure dynamics, influencing catalyst performance. Additionally, we uncovered a limitation in the coke resistance properties of the perovskite precursors where large NiFe nanoparticles showed considerable graphitic coke formation that limited the catalyst performance.…”
Section: Introductionmentioning
confidence: 87%
“…We examined the notion of bulk defect manipulation of perovskite oxide precursors to change the alloy composition, size, and shape of exsolved NiFe nanoparticles for DRM. 31 We found that the B-site metal redox properties can change nanoparticle formation and bulk crystal structure dynamics, influencing catalyst performance. Additionally, we uncovered a limitation in the coke resistance properties of the perovskite precursors where large NiFe nanoparticles showed considerable graphitic coke formation that limited the catalyst performance.…”
Section: Introductionmentioning
confidence: 87%
“…These two peaks correspond to the reduction of metal cations. The first peak is likely to be the reduction of Fe 3+ to Fe 2+ and Ni 3+ to Ni 2+ , whereas the second peak can be assigned to the further reduction to metallic phases . CGCO, on the other hand, is hardly reducible at temperatures less than 800 °C.…”
Section: Results and Discussionmentioning
confidence: 97%
“…The first peak is likely to be the reduction of Fe 3+ to Fe 2+ and Ni 3+ to Ni 2+ , whereas the second peak can be assigned to the further reduction to metallic phases. 41 CGCO, on the other hand, is hardly reducible at temperatures less than 800 °C. However, the synergistic effect of the LNF/CGCO composite would facilitate its reduction.…”
Section: Methodsmentioning
confidence: 93%
“…By controlling exsolution conditions, the size of the metal particles can be minimized to (i) maximize the dispersion of active sites, (ii) enhance synergistic interactions between the metal and the support, and (iii) suppress carbon deposition. [91,226] The most commonly studied perovskite-based dry reforming catalyst is LaNiO 3 , [92] whose performance can be further optimized through A-site and B-site substitution. For example, a post-exsolved LaNi 0.8 Mn 0.2 O 3 catalyst showed enhanced activity attributed to the MnO phase, which promoted CO 2 activation.…”
Section: Perovskite-based Catalystsmentioning
confidence: 99%
“…The post‐exsolution oxide structures act as supports as well as promoters for CO 2 activation. By controlling exsolution conditions, the size of the metal particles can be minimized to (i) maximize the dispersion of active sites, (ii) enhance synergistic interactions between the metal and the support, and (iii) suppress carbon deposition [91,226] …”
Section: Catalytic Systemsmentioning
confidence: 99%